PERCEPTIONS OF GRAMMARLY’S FREE VERSION AMONG INDONESIAN EFL UNDERGRADUATES: EVIDENCE FROM ARGUMENTATIVE ESSAY WRITING - Hanna Maryam Azzahra; Lilik Ulfiati; Duti Volya (English Language Education Program, Faculty of Education and Teacher Training, Sulthan Thaha Saifuddin State Islamic University of Jambi, 2026)
This study examined Indonesian sixth-semester EFL undergraduates' perceptions of Grammarly's free version and of their own argumentative essay quality, along with the relationship between the two. A quantitative, cross-sectional descriptive-correlational design was applied, involving 107 learners from a public university in Jambi Province selected through purposive sampling. Data were collected via a 28-item questionnaire assessing four Grammarly characteristics (spell-checker, grammar checker, punctuation, clarity) and seven argumentative-essay components, which were analyzed by descriptive statistics, Pearson correlation, and simple linear regression. Results showed learners had positive perceptions of Grammarly, nonetheless those perceptions varied by feature